Sosialisasi Pengenalan Aplikasi Canva dan Pelatihan Dasar Editing dalam Meningkatkan Kreativitas Bagi Siswa Kelas 5 MI Diponegoro 03 Karangklesem - Muhammad Zufron Shobriy; Naeli Zahrotun Nisa; Diatri Bunga Ramadhani; Laela Puji Astuti; Ito Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The creativity of elementary school students needs to be developed through the use of relevant technology. This study aims to describe the implementation of socialization on the introduction of the Canva application and basic editing training to enhance the creativity of 5th-grade students at MI Diponegoro 03 Karangklesem. A descriptive qualitative method was employed through observation and activity documentation. The activity was held on April 16, 2026, and was attended by 25 students. The results showed that students were able to understand the concept and function of Canva and successfully practiced creating simple designs such as posters. Students' enthusiasm and active participation during the activity indicate that Canva can improve creativity and learning motivation. This activity is recommended to be continued as part of the digital literacy program in elementary schools.